Three phase grid connected neutral point clamped (NPC) multilevel inverter fed by two wind turbines - Kamilu, Sanusi Alabi; Mekhilef, Saad (Universiti Putra Malaysia, 2019)
This paper presents two gear driven wind turbine generators (WTG) feeding a single three level grid connected NPC inverter. Each component of WTG is made up of wind turbine, 2-mass gear drive, permanent magnet synchronous generator (PMSG), AC-DC-AC power converter. A simple advanced hill climbs search (AHCS) maximum power point tracking algorithm that uses the mechanical power from the Wind turbine was developed to generate proper duty cycle for the control of single stage DC/DC boost converter. The DC link voltages are series interconnected and fed to a sinusoidal pulse width modulation (SPWM) controlled high power inverter. The complete model is simulated using MATLAB/ SIMULINK software under fixed and fluctuating wind speed conditions. Simulation results have shown that WECs exhibit variability in their output power as a result of changes in their prime movers (wind speed). © 2019, Universiti Putra Malaysia Press. All rights reserved.